On the existence of telescopers for mixed hypergeometric terms. (May 2015) - Chen, Shaoshi; Chyzak, Frédéric; Feng, Ruyong; Fu, Guofeng; Li, Ziming
Abstract: We present a criterion for the existence of telescopers for mixed hypergeometric terms, which is based on additive and multiplicative decompositions. The criterion enables us to determine the termination of Zeilberger's algorithms for mixed hypergeometric inputs, and to verify that certain indefinite sums do not satisfy any polynomial differential equation.